Temperature changes in the function of the shape inherent to the band of exciton absorption in nanofilm of layered semiconductor - Derevyanchuk, A.V.; Pugantseva, O.V.; Kramar, V.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Represented in this paper is the method and results of theoretical investigations aimed at the influence of spatial confinement effects, self-polarization of heterojunction planes as well as exciton-phonon interaction on the position and shape of the band corresponding to exciton absorption in nanofilms of layered semiconductor in a dielectric matrix. The heterojunction is considered as unloaded, the nanosystem is modeled by an infinitely deep quantum well and characterized by an essential difference between dielectric permittivities on both sides of the heterojunction. Calculated in this work are the dependences for the form-function of the absorption band on the thickness of lead iodide nanofilm embedded into polymer E-MAA or glass, and on its temperature. The results of calculations are in good accordance with known data of experimental measurements.